A Framework for AR Treasure Hunt Design - Chrisosthemos T., Vinicius; Pinho, Márcio Sarroglia (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
This paper proposes a framework for the development of Treasure Hunt games using Augmented Reality for educational purposes. The Framework is based on markers and allows the insertion of clues in the form of a simple instruction or an objective question with multiple choices along with 3D models anchored on the marker. Our main contribution was the development of a method for editing the game directly on the display device, without the need to adjust the content in a desktop editor and with low complexity of use. Overall, the framework was able to create Treasure Hunt applications in an easy and intuitive way.